A rapid method for detecting and distinguishing metallo-β-lactamase-and serine carbapenemase-producing Enterobacteriales using MALDI-TOF MS - Jing, Xiaopeng; Hu, Yanyan; Wu, Tingting; Zhang, Xing; Luo, Shaofeng; Wang, Wei; Min, Xiaochun; Sun, Ruiling; Zeng, Ji (Frontiers in Microbiology, 2023)
Carbapenemase-producing Enterobacteriales (CPE) are a major health threat worldwide, and therefore the development of rapid detection methods is needed. Here, we established a method to distinguish metallo-β-lactamase and serine carbapenemases using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) with ethylenediaminetetraacetic acid (EDTA) and phenylboronic acid (PB). To assess the specificity and sensitivity of the method, 110 carbapenemase-producing and 72 carbapenemase-negative Enterobacteriales isolates were collected, among which 51 strains produced only metallo-β-lactamase, 55 strains only serine carbapenemases, and four strains both metallo-β-lactamase and serine carbapenemases. In the proposed MALDI-TOF MS method, imipenem (IPM) and the bacterial strains to be tested were mixed, EDTA and/or PB was added, and the mixture was incubated for 4 h. The carbapenemase type was confirmed by the IPM waveform spectrum before and after incubation. Based on the presence, absence, and recovery of the IPM-cyano-4-hydroxy-cinnamic acid-specific waveform peak near 479 m/z, the detection sensitivity and specificity of the method were 98.2% and 100%, respectively. Although CPE detection by MALDI-TOF MS has been studied previously, our method distinguishes between metallo-β-lactamase and serine carbapenemases, which will be very helpful for the clinical selection of antibiotics.